Analysis of The Rationalization of Rainfall Stations in The Kayan River Basin, North Kalimantan Province - Fadzil Abdillah; Hanie Teki Tjendani; Esti Wulandari (Publica Scientific Solution, 2026)
The Kayan River Basin (Wilayah Sungai [WS]) covers an area of 3,178,215.72 hectares, making it one of the largest river basins in Kalimantan. However, compared with other river basins in the region, the Kayan WS currently has only seven rainfall stations, of which six are operational and one is damaged or inactive. This limited observation network is insufficient to represent the highly heterogeneous spatial distribution of rainfall across the basin, which extends from mountainous upstream areas with high precipitation to lowland coastal regions. Therefore, this study aims to determine the most appropriate rationalization method for identifying the optimal number and spatial distribution of rainfall stations capable of adequately representing rainfall variability within the Kayan River Basin. Three approaches were evaluated for rainfall station rationalization: the maximum requirement method, the minimum requirement method, and the Kagan–Rodda method. The results indicate that the Kagan–Rodda method is the most suitable approach for rationalizing the rainfall station network in the Kayan WS. Based on this method, the basin requires a total of 33 rainfall stations. Given that only six operational stations currently exist, an additional 27 rainfall stations are required to establish an optimal monitoring network.